2017
DOI: 10.1002/chem.201704715
|View full text |Cite
|
Sign up to set email alerts
|

Refreshing Rubbers as Customized Photothermal Conversion Materials through Post‐Darkening Modeling Production

Abstract: Organic conjugated polymers with low energy bandgaps are emerging as a particular class of near-infrared (NIR) photothermal conversion materials. However, these polymers routinely possess high phase transition temperatures due to the rigid skeleton and strong intermolecular interactions. Conjugated polymers can rarely be thermally processed at low temperature, especially below 100 °C. This work formulates a concept of post-darkening modeling production (p-DMP) by which the thermoplastic non-conjugated trans-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The motivation started originally from the formulation of a processable photothermal dark material. 2 The photothermal materials developed focus mainly on carbon-based and metal-based materials and conjugated polymers. They are not preferable for additive manufacturing for customized production in terms of the rigidity in chemical structure or high melting point.…”
Section: Activation and Stabilization Of Iodinementioning
confidence: 99%
“…The motivation started originally from the formulation of a processable photothermal dark material. 2 The photothermal materials developed focus mainly on carbon-based and metal-based materials and conjugated polymers. They are not preferable for additive manufacturing for customized production in terms of the rigidity in chemical structure or high melting point.…”
Section: Activation and Stabilization Of Iodinementioning
confidence: 99%
“…Previously, we have proposed a method for darkening trans ‐polyisoprene (TPI) as a kind of 3D‐printable photothermal materials by iodine doping . The study revealed that radical cations formed on TPI polymer backbones after the darkening treatment, which partially accounted for the wide absorption in visible‐ and near‐infrared‐light windows.…”
Section: Figurementioning
confidence: 99%
“…It is also convenient to locate the light energy in a targeting space without causing bulky interference . The photothermal conversion ability of iodine‐doped TPI, through which light energy could be converted to thermal heat, has been tested . In this regard, it is assumed that light irradiation may induce the “killing and releasing” strategy as the variation of temperature did.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations